The Learning Communities Scientific Calculator (LCSC) 45 Webinar on Problem-Solving in Mathematics - Safarini, Desyarti (Center for Research and Community Service of Sampoerna University, 2021)
The LCSC 45 webinar was a joint community service activity between Casio Education Indonesia and Sampoerna University. This activity was held in the form of online sharing session for mathematics teachers, with the topic Problem-Solving in Mathematics. The LCSC 45 webinar aimed to share ideas and build awareness of the importance of Problem-Solving in Mathematics. Most participants were very satisfied with the speaker’s facilitation and sure that they understood mathematical problem-solving. The webinar activities were rated as attractive because of its rich contents, challenging problem-solving questions, the use of Padlet and sharing links via barcode. However, some obstacles were still encountered, such as unstable internet connections and limited webinar time duration. For future improvement, it was suggested to fully assist teachers in designing and implementing problem-solving in a mathematics lesson.